LncRNA AATBC regulates Pinin to promote metastasis in nasopharyngeal carcinoma. Issue 9 (13th June 2020) - Tang, Ting; Yang, Liting; Cao, Yujian; Wang, Maonan; Zhang, Shanshan; Gong, Zhaojian; Xiong, Fang; He, Yi; Zhou, Yujuan; Liao, Qianjin; Xiang, Bo; Zhou, Ming; et al.
Abstract : Long noncoding RNA (lncRNA) have emerged as crucial regulators for a myriad of biological processes, and perturbations in their cellular expression levels have often been associated with cancer pathogenesis. In this study, we identified AATBC (apoptosis‐associated transcript in bladder cancer, LOC284837) as a novel lncRNA. AATBC was found to be highly expressed in nasopharyngeal carcinoma (NPC), and increased AATBC expression was associated with poor survival in patients with NPC. Furthermore, AATBC promoted migration and invasion of NPC cells in vitro, as well as metastasis in vivo . AATBC upregulated the expression of the desmosome‐associated protein pinin (PNN) through miR‐1237‐3p sponging. In turn, PNN interacted with the epithelial–mesenchymal transition (EMT) activator ZEB1 and upregulated ZEB1 expression to promote EMT in NPC cells. Collectively, our results indicate that AATBC promotes NPC progression through the miR‐1237‐3p–PNN–ZEB1 axis. Our findings indicate AATBC as a potential prognostic biomarker or therapeutic target in NPC. Abstract : Tang et al . found a novel lncRNA, AATBC, was upregulated in nasopharyngeal carcinoma (NPC) and associated with poor prognosis. Moreover, in vitro and in vivo experiments confirmed that AATBC promoted migration and invasion of NPC cells through sponging miR‐1237‐3p and upregulating PNN. In turn, PNN interacted with the ZEB1 and activated epithelial–mesenchymal transition in NPC cells.